Depression, anxiety and fear of missing out as correlates of social, non-social and problematic smartphone use. (June 2020) - Elhai, Jon D.; Gallinari, Elizabeth F.; Rozgonjuk, Dmitri; Yang, Haibo
Highlights: Non-social smartphone use (NSSU) related to fear of missing out (FOMO). NSSU related to problematic smartphone use (PSU) severity. FOMO mediated relations between depression severity and NSSU. FOMO mediated relations between both depression and anxiety with PSU severity. Abstract: Few studies have examined mental health variables in relation to social vs. non-social smartphone use, and how such types of use relate to problematic smartphone use (PSU). We conducted a web survey of 316 American undergraduate students about severity of depression, anxiety, fear of missing out (FOMO), social and non-social smartphone use, and PSU. Using structural equation modeling, we found that compared to social smartphone use, non-social use was more strongly linked with severity of PSU (β = 0.18, p < .05) and FOMO (β = 0.24, p < .05). FOMO mediated relations between depression severity and non-social smartphone use (β = 0.09, p = .04). Furthermore, FOMO mediated relations between both depression (β = 0.23, p < .001) and anxiety (β = 0.16, p = .04) with PSU severity. We discuss non-social smartphone use as a possible avoidance strategy among anxious individuals, and the role of FOMO in individuals desiring social connectedness but also feeling socially anxious. Results are discussed in the context of a comprehensive theoretical model on pathways toward excessive internet use.